Nonlinear effects of digitalization on export activities: an empirical investigation in European countries - Nham, Nguyen Thi Hong; Bao, Nguyen Khac Quoc; Ha, Le Thanh (Technological and Economic Development of Economy, 2023)
Our study is the first to empirically analyze the nonlinear relationship between digitalization and export value and diversification. This paper measures the digital transformation process in terms of digital connectivity, uses of the internet, e-business, e-commerce, and e-government. The various econometrics techniques are applied for the database of 23 European countries during the period 2015–2020. The vital findings should be conveyed here. First, the bottlenecks of export values could be resolved by promoting digital transformation. However, the non-linear reverted U-shaped relationship between digitalization and export diversification suggests that positive effects only appear when the digital activities, especially in digital connectivity, humans with digital skills, use of internet services, or digital public services reaches a certain threshold. Second, the positive influence of digitalization on exports stems from a reduction in export cost and export time to deal with documentary and border compliance as well as improvements in competence and quality of logistic services and quality of trade and transport-related infrastructure, thus enhancing exports. Third, the role of digital connectivity and the integration of digital technology into business and commerce become especially important for export diversification.